PENGARUH PENGUNGKAPAN CSR DAN TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN SEKTOR INDUSTRI SUB SEKTOR TEKSTIL DAN GARMEN - Farah Latifah Nurfauziah; Citra Kharisma Utami (Jurnal Akuntansi, 2021)
The purpose of this study was to determine the effect of Corporate Social Responsibility Disclosure and Good Corporate Governance on Firm Value in Various Industries Sector, Textile and Garment Sub-Sector Listed on the Indonesia Stock Exchange 2014-2019 Period. This research method uses a descriptive method with a quantitative approach. The source of this research uses secondary data sourced from the annual report of various sector companies in the textile and garment sub-sector listed on the Indonesia Stock Exchange. The sample of this study were 9 companies using purposive sampling technique. The results of this study indicate that partially the Corporate Social Responsibility Disclosure has a significant effect on Firm Value. Meanwhile, Good Corporate Governance with indicators (Managerial Ownership, Institutional Ownership, Independent Ownership and Audit Committee) Managerial Ownership and Audit Committee have a significant effect on Firm Value, while Institutinal Ownership and Independent Comissioner don’t have a significant effect on Firm Value.